A performance of hybrid biosorbent ‘M-Bios’ of Pb(II) and Cu(II) in aqueous solutions - Kamal, Mohd Lias; Tajam, Jamil; Hasan, Sharizal; Ismail, Mohd Halim Shah; Mohd Naspu, Anies Suhaida; Zahala, Nur Saliza Awatif (International Journal of Scientific and Research Publications, 2014)
‘M-bios’ biosorbent is a hybrid of mangrove wasted bark from charcoal industry at Perak, Malaysia and green algae from Sabah to remove heavy metals. This biosorbent is subjected to FTIR and ICP-MS. ‘M-Bios’ contain N – H (3421.89 cm-1, 3465.90 cm-1), C = O (1728.72 cm-1) and – OH (3531.37 cm-1, 3722.01 cm-1, 3768.36 cm-1) functional groups (weak groups) that that easily replaced by metal ions. The adsorption performances were fitted by pseudo-kinetic, Langmuir and Freundlich study. The plots obey both adsorption isotherm models, Langmuir and Freundlich by R2 values. A good agreement between experimental and theoretical qe for contact time data suggested that adsorption reaction happen in aqueous solution was a rate determination of chemisorption process(pseudo second-order kinetic).